Evaluasi Manajemen Logistik Alat Kesehatan Di Puskesmas X Kabupaten Tegal - Sekawanie, Denayu; Arumsari, Wahyuni; Marchamah, Dwi Nur Siti (Universitas Ivet, 2025)
Special officers who manage medical devices delegate their duties in each area so that the officers do not know which devices are still functioning or not, and officers are still concurrently with other duties concurrently. The study aims to determine the logistics management of medical devices at Community Health Center X, Tegal Regency. The study used a qualitative method with seven informants, including the general administration section and holders of facilities, infrastructure, and medical device applications, technical officers, laboratory sections, dental and oral sections, delivery rooms, financial holders, and the head of administration. Data collection was carried out using observation, interviews, and documentation methods. The results of the study showed that there were still obstacles 46% for facilities and infrastructure, and 14% for medical devices. Human resources managing medical device logistics were mostly still concurrently held by general administration officers. The use of medical devices at Community Health Center X, Tegal Regency, has been running well, but for maintenance, there is no special officer tasked with maintaining equipment with routine checks. It is hoped that future researchers can conduct more in-depth research to obtain supporting data and avoid gaps during interviews.